2021
DOI: 10.1126/sciadv.abf6935
|View full text |Cite
|
Sign up to set email alerts
|

A biomarker-authenticated model of schizophrenia implicating NPTX2 loss of function

Abstract: CSF NPTX2 is a biomarker of schizophrenia and supports a model that integrates across genetics, pharmacology, and behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 64 publications
(117 reference statements)
2
25
0
Order By: Relevance
“…Nptx2 KO mice parallel the phenotype of C4-overexpressing mice; we found elevated levels of cleaved C4b in brains from Nptx2 KO mice and we previously reported that Nptx2 KO mice exhibit increased vulnerability to social isolation stress with emergent neuropsychiatric behavioral deficits (Xiao et al, 2021). The present finding extends the notion that Nptx2 loss of function spans the complex genetics of schizophrenia as a shared common pathway (Xiao et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Nptx2 KO mice parallel the phenotype of C4-overexpressing mice; we found elevated levels of cleaved C4b in brains from Nptx2 KO mice and we previously reported that Nptx2 KO mice exhibit increased vulnerability to social isolation stress with emergent neuropsychiatric behavioral deficits (Xiao et al, 2021). The present finding extends the notion that Nptx2 loss of function spans the complex genetics of schizophrenia as a shared common pathway (Xiao et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…In AD, Nptx2 is decreased in postmortem brain and in patient CSF where its levels correlate with disease status, cognitive performance and disease progression (Xiao et al, 2017). Nptx2 levels are also reduced in CSF from schizophrenia patients, and Nptx2 knockout (Nptx2 KO ) mice show schizophrenia-related behavioral deficits (Xiao et al, 2021). Given the identification of Nptx2 as a regulator of complement, we next examined if Nptx2 KO mouse brains exhibited dysregulated complement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EGR2 [99], ADCYAP1 [100], CHRNA7 [101], NRN1 [102], ETV5 [103], STXBP1 [104], CAMKK2 [105], VAMP2 [106], SYNGR1 [107], NOD2 [108], TLR2 [109], BRCA2 [110] and LEF1 [111] were previously reported to be critical for the development of bipolar disorder. Accumulating evidence shows that EGR2 [112], WNT1 [113], ARC (activity regulated cytoskeleton associated protein) [114], ADCYAP1 [115], SCN5A [116], RTN4R [117], CHRNA7 [118], NRGN (neurogranin) [119], CHRM1 [120], CCK (cholecystokinin) [121], RGS4 [122], LINGO1 [123], PAK1 [124], PCDH19 [125], NRN1 [126], CX3CL1 [127], CNTNAP2 [128], SLC12A5 [129], GAS7 [130], NTNG1 [131], RAB3A [132], STXBP1 [104], CHRNB2 [133], CDK5 [134], HTR5A [135], SLC30A3 [136], HTR3B [137], HTR2C [138], TAMALIN (trafficking regulator and scaffold protein tamalin) [139], STX1A [140], GRM2 [141], SLC1A6 [142], NPTX2 [143], CAMKK2 [144], SYP (synaptophysin) [145], VAMP2 [146], ATP1A3 [147], SV2A [148], CNTNAP2 [149], CAP2[150], SYNGR1 [151], SNCB (synuclein beta) [152], RBP4 [153], KIF17 [154], CHI3L1 [155], CCR5 [156], C1QB [157], TLR7 [158], TLR2 [159], MNDA (myeloid cell nuclear differentiation antigen) [160], C3 [161], IL2RG [162], MICB (MHC class I polypeptide-related sequence B) [163], FKBP5 [164], NEFH (neurofilament heavy chain) [165], CELSR1 [166], APBB1IP [167], CD34 [168], BRCA2 [110], ITGB3 […”
Section: Discussionmentioning
confidence: 99%